Epigenetic Regulation of Hepatic Lipogenesis: Role in Hepatosteatosis and Diabetes - Viscarra, Jose (Diabetes, 2020)
Hepatosteatosis, which is frequently associated with development of metabolic syndrome and insulin resistance, manifests when triglyceride (TG) input in the liver is greater than TG output, resulting in the excess accumulation of TG. Dysregulation of lipogenesis therefore has the potential to increase lipid accumulation in the liver, leading to insulin resistance and type 2 diabetes. Recently, efforts have been made to examine the epigenetic regulation of metabolism by histone-modifying enzymes that alter chromatin accessibility for activation or repression of transcription. For regulation of lipogenic gene transcription, various known lipogenic transcription factors, such as USF1, ChREBP, and LXR, interact with and recruit specific histone modifiers, directing specificity toward lipogenesis. Alteration or impairment of the functions of these histone modifiers can lead to dysregulation of lipogenesis and thus hepatosteatosis leading to insulin resistance and type 2 diabetes.